CYTOGENETICS EFFECTS OF ADRIAMYCIN IN BONE MARROW CELLS OF SWISS ALBINO MICE - C. KUSUM LATA; K. RUDRAMA DEVI (The Bioscan, 2010)
In present investigation the cytogenetic effect of Adriamycin were studied in invivo animal model by using analysis of chromosomal aberration in somatic cells of mice. Three concentration were selected and used to analysisthe frequency of chromosomal aberration .As the concentration increased a significant increase in the frequency of chromosomal aberration in somatic cells of Adriamycin treated mice was observed thus the results indicate the clastogenetic nature of adriamycin in mice.